(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
All parts of the yellow oleander are toxic, but the roots and seeds are more toxic compared to other parts. Yellow oleander plants are more toxic than Nerium oleander. [1] Yellow oleander is an ornamental plant that belongs to the family Apocynaceae and is native to Mediterranean regions of Europe and Asia. It is cultivated in tropical and subtropical areas of the world. Introduction Yellow oleander, with a scientific name “Thevetia peruviana [3],” is known as the “Suicide Tree” because all parts of the tree are poisonous. The usual fatal dose of yellow oleander is 8 to 10 seeds, and the roots are around 15 to 20 grams. The most common manifestations associated with yellow oleander poisoning include bradycardia with AV block, hypertension, lethargy, dizziness, and GI distress. Convulsions, electrolyte disturbances, hypertension, and coma have been reported. Management includes gastric decontamination, specific antidotes anti-digoxin Fab and Fructose 1, 6 diphosphate administration, cardioversion, and cardiovascular supportive care. [2, 3]We came across a case of suicidal poisoning with pila kaner, anuncommon occurrence even for a major referral hospital such as ours, Rajindra Hospital Patiala (Government Medical College Patiala).